Interview with professor Dirk Geeraerts - Wiedemer, Marcos Luiz; Rosário, Ivo da Costa do (SOLETRAS, 2014)
Dirk Geeraerts is professor of linguistics at the University of Leuven, Belgium, and his main research interests involve the fields of lexical semantics, lexicology, and lexicography, with a focus on social variation and diachronic change. His theoretical orientation is mainly that of Cognitive Linguistics, with an emphasis on empirical methods for linguistic analysis. He is the founder of the journal Cognitive Linguistics and he is the editor, with Hubert Cuyckens, of The Oxford Handbook of Cognitive Linguistics. Since 2005, he is managing editor of Mouton de Gruyter’s Cognitive Linguistics Research series.